Association of oral health literacy with oral health behavior and oral health outcomes among adult dental patients - Jagadeeswara Rao Sukhabogi; Dolar Doshi; Madhuri Vadlamani; Vijay Rahul (Wolters Kluwer Medknow Publications, 2020)
Aims: To evaluate the association of oral health literacy (OHL) with oral health behavior and oral health outcomes among dental patients in Hyderabad City. Settings and Design: Cross-sectional study among dental patients. Materials and Methods: A convenience sample of 605 adults >18 years of age visiting the out-patient Department of Public Health Dentistry of Government Dental College and Hospital, Hyderabad, were recruited. The five-item scale developed by Ishikawa was used to measure communication and critical OHL. Socioeconomic status was assessed using Modified Kuppuswamy's scale and questions for oral health behavior included frequency of toothbrushing, frequency of dental visit, and reason for visit. Dentition status, periodontal status, and loss of attachment were recorded according to World Health Organisation Survey methods. Statistical Analysis Used: Frequency distribution was done and association between the variables and predictors (oral health behavior and oral health status) of OHL was calculated using odds ratio. Results: The mean age of the study population was 31.5 + 11.2 years. None of the individuals' questions of OHL questionnaire had 50% response of strongly agree or agree. The oral health parameters of decayed and filled teeth emerged as a significant predictor for model 1 (adjusted by sex and age) and model 2 (adjusted by sex, age, and social class). Likewise, toothbrushing frequency was significantly associated with low OHL. Conclusions: This study shows a high prevalence of low OHL in the study population, with decayed teeth and filled teeth and oral health behavior like toothbrushing only once as a significant predictor for low OHL.